The emergence of age‐dependent social cognitive deficits after generalized insult to the developing brain: A longitudinal prospective analysis using susceptibility‐weighted imaging. Issue 5 (23rd December 2014) - Ryan, Nicholas P.; Catroppa, Cathy; Cooper, Janine M.; Beare, Richard; Ditchfield, Michael; Coleman, Lee; Silk, Timothy; Crossley, Louise; Beauchamp, Miriam H.; Anderson, Vicki A.
Abstract Childhood and adolescence are critical periods for maturation of neurobiological processes that underlie complex social and emotional behavior including Theory of Mind (ToM). While structural correlates of ToM are well described in adults, less is known about the anatomical regions subsuming these skills in the developing brain or the impact of cerebral insult on the acquisition and establishment of high‐level social cognitive skills. This study aimed to examine the differential influence of age‐at‐insult and brain pathology on ToM in a sample of children and adolescents with traumatic brain injury (TBI). Children and adolescents with TBI (n = 112) were categorized according to timing of brain insult: (i) middle childhood (5–9 years; n = 41); (ii) late childhood (10–11 years; n = 39); and (iii) adolescence (12–15 years; n = 32) and group‐matched for age, gender, and socioeconomic status to a typically developing (TD) control group (n = 43). Participants underwent magnetic resonance imaging including a susceptibility‐weighted imaging (SWI) sequence 2–8 weeks postinjury and were assessed on a battery of ToM tasks at 6‐ and 24‐months after injury. Results showed that for adolescents with TBI, social cognitive dysfunction at 6‐ and 24‐months postinjury was associated with diffuse neuropathology and a greater number of lesions detected using SWI. In the late childhood TBI group, we found a time‐dependent emergence of social cognitive impairment, linked to diffuse neuropathology. The middle childhood TBI group demonstrated performance unrelated to SWI pathology and comparable to TD controls. Findings indicate that the full extent of social cognitive deficits may not be realized until the associated skills reach maturity. Evidence for brain structure–function relationships suggests that the integrity of an anatomically distributed network of brain regions and their connections is necessary for the acquisition and establishment of high‐level social cognitive skills. Hum Brain Mapp 36:1677–1691, 2015. © 2014 Wiley Periodicals, Inc.